Analysis of the Influence of Influencer Endorsement, Fashion Trends, and Prices on Fashion Product Purchase Decisions on TikTok Shop. - purnomo, helmi; Joko Soeprijatno, Edy (Proceeding Kilisuci International Conference on Economic & Business, 2025)
Abstract Research purposes:Analyzing the significant influence of influencer endorsement, fashion trends, and prices on purchasing decisions for fashion products on TikTok Shop. Design/Method/Approach:This study uses a quantitative approach to analyze the collective influence of influencer endorsement, fashion trends, and prices on purchasing decisions for fashion products on TikTok Shop. Data were collected through a survey using a structured questionnaire designed based on research variable indicators. Research Findings:Significant Influence of Independent Variables, Novelty in Comprehensive Model, Theoretical and Practical Contributions Theoretical contribution/Originality:Comprehensive Model Integration, Synergy of Social and Economic Factors Implications for Practice / Policy:Optimizing Influencer Marketing Strategy, Competitive Pricing Research limitations:Limited Platform Context, Quantitative Approach